Pengaruh Strategi Pemasaran 4P Terhadap Keputusan Pembelian Produk Pulsa21 Di Kabupaten Gresik - Winda Sari; Bambang Karnain P; Achmad Daeng GS; Sugiharto Sugiharto; Rina Dewi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of the 4P marketing strategy on purchasing decisions for Pulses21 products in Gresik district. This type of research used is quantitative research. The population in this study was around 15,000 people with a sample of 100 respondents. Data was collected through questionnaires and observation methods. The data analysis technique used is the classical assumption test which consists of a normality test, multiple linear regression analysis, and hypothesis testing, namely the t test, F test, and the coefficient of determination (R²). The results of the data analysis obtained a simple linear equation Y=1.198+0.196X1+0.457X2+(-0.078X3)+0.315X4+0.267. The conclusion that can be drawn from this study is that the marketing strategy variable price and promotion have a significant influence on purchasing decisions while the product and place variables do not have a significant influence on purchasing decisions. This is evident from the t count > t table, namely for the price variable 4.224> 1.985 with a significance value of 0.001˂0.05 and the promotion variable 2.964˃1.985 with a significance value of 0.004˂0.05, while for the product variable it is 1.581˂1.985 with a significance value of 0.117˃0.05 and the place variable -0.722˂1.985 with a significance value of 0.472˃0.05. And the results of the F test analysis obtained a calculated F value of 65.069 which was greater than the F table of 2.47 and an F significance of 0.001 which was smaller than 0.05. The calculation results for the R2 value are 0.733 which means that the 4P variables have an influence on purchasing decisions of 73.3%, while the remaining 26.7% is influenced by other variables not examined in this study.